Integrating Adolescent Mental Health into HIV Prevention and Treatment Programs: Can Implementation Science Pave the Path Forward? - Boshe, Judith; Brtek, Veronica; Beima-Sofie, Kristin; Braitstein, Paula; Brooks, Merrian; Denison, Julie; Donenberg, Geri; Kemigisha, Elizabeth; Memiah, Peter; Njuguna, Irene; Poku, Ohemaa; Roberts, Sarah T.; et al. (AIDS and Behavior, 2023)
Adolescent mental health (AMH) is a critical driver of HIV outcomes, but is often overlooked in HIV research and programming. The implementation science Exploration, Preparation, Implementation, Sustainment (EPIS) framework informed development of a questionnaire that was sent to a global alliance of adolescent HIV researchers, providers, and implementors working in sub-Saharan Africa with the aim to (1) describe current AMH outcomes incorporated into HIV research within the alliance; (2) identify determinants (barriers/gaps) of integrating AMH into HIV research and care; and (3) describe current AMH screening and referral systems in adolescent HIV programs in sub-Saharan Africa. Respondents reported on fourteen named studies that included AMH outcomes in HIV research. Barriers to AMH integration in HIV research and care programs were explored with suggested implementation science strategies to achieve the goal of inte¬grated and sustained mental health services within adolescent HIV programs.
Keywords: Adolescent; Mental health; HIV; Sub-Saharan Africa; Implementation science research